Les femmes qui restent, ressorts de l’économie familiale d’archipel au Mexique - Aurélia Michel (EchoGéo)
In the rural southwest of Mexico, migrations in the national space and beyond the frontier are common experiences accumulated by most of the families since the 1940’s. Meanwhile, a big agrarian reform had been applied with important effects on the anchorage of these families in their rural place. Therefore, families have evolved as kinds of archipelagos at regional scale. Now the ties that bind the members of theses archipelagos are especially invested and maintained by women, because of several factors that are detailed in this paper. In the meantime, economic recognition of the woman’s contribution to family, women’s access to employment, distance, all lead to promote women’s access to land. The analysis of these trends comes from the observation of various individual and family paths in Zanatepec, in the south of Oaxaca.